2023
DOI: 10.1002/jms.4953
|View full text |Cite
|
Sign up to set email alerts
|

Thermal desorption direct analysis in real‐time high‐resolution mass spectrometry and machine learning allow the rapid authentication of ground black pepper and dried oregano: A proof‐of‐concept study

Carmela Zacometti,
Andrea Massaro,
Tommaso di Gioia
et al.

Abstract: Thermal desorption direct analysis in real‐time high‐resolution mass spectrometry (TD‐DART‐HRMS) approaches have gained popularity for fast screening of a variety of samples. With rapid volatilization of the sample at increasing temperatures outside the mass spectrometer, this technique can provide a direct readout of the sample content with no sample preparation. In this study, TD‐DART‐HRMS's utility for establishing spice authenticity was examined. To this aim, we directly analyzed authentic (typical) and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…With the HS-GC-IMS method of this paper, 100% of genuine or adulterated oregano samples are successfully classified, and, in contrast to the last cited article, the percentage of adulterants can be quantified. In the same way, reported ambient mass spectrometry methods have not been able to determine the amount of adulteration [5,17,18]. DNA-based methods are more time-consuming, and in some cases, if the presence of the adulterant is detected, it can be due to an "(insignificant) trace contamination" [25].…”
Section: Analysis Of Commercial Oregano Samples and Comparison With O...mentioning
confidence: 99%
See 1 more Smart Citation
“…With the HS-GC-IMS method of this paper, 100% of genuine or adulterated oregano samples are successfully classified, and, in contrast to the last cited article, the percentage of adulterants can be quantified. In the same way, reported ambient mass spectrometry methods have not been able to determine the amount of adulteration [5,17,18]. DNA-based methods are more time-consuming, and in some cases, if the presence of the adulterant is detected, it can be due to an "(insignificant) trace contamination" [25].…”
Section: Analysis Of Commercial Oregano Samples and Comparison With O...mentioning
confidence: 99%
“…In a recent work, Creydt et al [16] identified blumeatin as a marker to identify some common oregano adulterants using ion mobility MS coupled to LC. Other techniques that have been employed with the same purpose are direct analysis in real-time and an atmospheric solid analysis probe coupled to (HR)MS [5,17,18], proton nuclear magnetic resonance spectroscopy [19,20], photoacoustic laser spectroscopy [21], DNA-based methods [8,20,[22][23][24][25] and near-infrared spectroscopy (NIR) [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%